Literasi Finansial, Kesadaran Digital, Posisi Manajerial: Sebuah Bukti dari Riset Keuangan - Marthinus Ismail; Lorina Siregar Sudjiman; Rolyana Ferinia (Coopetition : Jurnal Ilmiah Manajemen, 2023)
Everyone requires good digital awareness in the industrial era 4.0, where the digital role is attached to every financial activity. As a result, the goal of this study is to examine the impact of financial literacy on digital awareness. partially, the effect of financial literacy on managerial positions, and see the effect of financial literacy on digital awareness through managerial positions. This study was guided by a quantitative method with a correlational design and logistic regression data analysis. The sample used was a convenience sample, with 239 Adventist University of Indonesia alumni filling out the questionnaire. Partially, no significant effect was found between financial literacy and managerial position, but the mediating variable "managerial position" can increase financial literacy. Managers play an important role in increasing financial literacy and providing employees with optimal digital awareness.